Illegal Migrant Youth’ engagement into risky behaviours for their sustainable livelihoods: The Case of Musina town in the Limpopo Province of South Africa - Ramoshaba, Dillo Justin; Rapholo, Selelo Frank; Mamadi, Khutso (Technium Social Sciences Journal, 2022)
Several studies show that immigration is a global challenge. Some studies in South Africa where this study was conducted reveal youth as making an increased number of international migrant population. Upon their arrival in the country, migrant youth face a vast number of challenges such as extreme poverty and the exclusion from the welfare services. As a result of these, migrant youth resort to risky behaviours for their survival and sustainable livelihoods during their stay in the country. It is from this background that the study sought to scientifically explore the risky behaviours that migrant youth’ engage into for their sustainability. The study used a qualitative approach wherein Musina was used as a case study. Ten migrant youths were purposively and conveniently selected to participate in this study. Data was collected through face to face semi-structured interviews and analysed thematically through the assistance of the Nvivo software. Resilience theory was used to guide this study. Findings reveal that migrant youths in Musina town engage into risky behaviours such as crime, sex work, cheap and exploitative labours for their sustainable livelihoods. It is recommended that to mitigate these risky behaviours perpetuated by illegal migrant youth, the security, screening and vetting should be tightened at the border posts.